The deep structure of the Jewish portable sanctuary - Debevec, Leon (Edinost in dialog, 2023)
The architectural image of the Jewish portable sanctuary is the problem framework of the paper. The conviction that the sacred tabernacle, as a work of God, is a complete work of art leads to a search for starting points to discover the uniqueness of its in-depth structure. The research established two: the first is the preparation of an authentic architectural scheme of the Jewish portable sanctuary as a basis for compositional analyses. The second is dictated by the determination of the possible presence of a compositional tools which manifests itself mainly in the use of proportions. The perceptible richness of the presence of almost the entire range of harmonic proportions is revealed in the texts discussed. Their abundance and affinity dispel the suspicion of accidental presence in the underlying tissue of the architectural image of the portable sanctuary. They rather point to the enviable building skills of the priestly elite and their concern to protect this knowledge from the uninitiated.
Keywords: architecture; arhitektura; composition; Eksodus; Exodus; harmonične proporcije; harmonious proportions; kompozicija; Mojzes; Moses; sacred tent; sveti šotor